ST Segment Elevation Besides Acute Myocardial Infarction - Alam, Md Zahid; Ara, Rowsan; Rahaman, Mohammad Ferdous Ur; Ahsan, Hafez Mohammad Nazmul; Salman, Mohammad; Shefa, Jannatara (University Heart Journal, 2012)
ST segment elevation (STE) in electrocardiography (ECG) commonly denotes acute myocardial infarction (AMI)1,2. As AMI needs prompt diagnosis and specific treatment like thrombolysis, anticoagulation or primary percutaneous coronary intervention (PCI) which significantly improve outcome1, recognition of other conditions where STE also occurs are equally important to avoid potential hazards. This review points out to such conditions of ECG tracing. DOI: http://dx.doi.org/10.3329/uhj.v8i1.11667 University Heart Journal Vol. 8, No. 1, January 2012